2002
DOI: 10.1530/eje.0.1460707
|View full text |Cite
|
Sign up to set email alerts
|

SOM230: a novel somatostatin peptidomimetic with broad somatotropin release inhibiting factor (SRIF) receptor binding and a unique antisecretory profile

Abstract: Objective: The aim of the present study was to identify a small, metabolically stable somatotropin release inhibiting factor (SRIF) analog with a more universal binding profile similar to that of natural somatostatin, resulting in improved pharmacological properties and hence new therapeutic uses. Design: A rational drug design approach was followed by synthesizing alanine-substituted SRIF-14 analogs to determine the importance of single amino acids in SRIF-14 for SRIF receptor subtype binding. The incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
433
0
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 633 publications
(467 citation statements)
references
References 38 publications
14
433
0
13
Order By: Relevance
“…While earlier studies reported a high success rate for firstgeneration SSAs, octreotide and lanreotide (3,4), more recent studies show that control of growth hormone (GH) and insulin-like growth factor 1 (IGF1) levels using stricter criteria is achieved in !40% of patients (5,6). Pasireotide is a multireceptor-targeted SSA that binds SSTR1, SSTR2, SSTR3 and SSTR5, with the highest affinity for SSTR5 (7). Pasireotide normalizes IGF1 in a higher proportion of patients compared to first-generation SSAs and in up to 20% of patients who are inadequately controlled on firstgeneration SSAs (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies reported a high success rate for firstgeneration SSAs, octreotide and lanreotide (3,4), more recent studies show that control of growth hormone (GH) and insulin-like growth factor 1 (IGF1) levels using stricter criteria is achieved in !40% of patients (5,6). Pasireotide is a multireceptor-targeted SSA that binds SSTR1, SSTR2, SSTR3 and SSTR5, with the highest affinity for SSTR5 (7). Pasireotide normalizes IGF1 in a higher proportion of patients compared to first-generation SSAs and in up to 20% of patients who are inadequately controlled on firstgeneration SSAs (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the inhibitory effect of SST can be either direct inhibition of cell proliferation, or indirect via inhibition of secretion of growth-inducing hormones or inhibition of angiogenesis (2). SST acts through five high-affinity, G protein-coupled membrane receptors, which are variably expressed in both normal tissues and tumours; the analogue octreotide activates SST receptor subtype-2 (SSTR2) and to a lesser extent SSTR5, while the new SST analogue SOM230 (pasireotide) activates SSTR1, 2, 3 and 5 receptors, with varying affinity (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Pasireotide is a somatostatin analog, which binds sst 1, 2, 3, 5 with high affinity (Bruns et al 2002). In particular, it has subnanomolar affinity for the sst 5 , the predominant sst in corticotroph pituitary adenomas (Bruns et al 2002, Hofland et al 2005.…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%